Gyrfalcon Falco rusticolus from an Uyghur well in Karabalgasun (Ordu-Baliq), Central Mongolia ... : Gyrfalcon Falco rusticolus from an Uyghur well in Karabalgasun (Ordu-Baliq), Central Mongolia ... - Töpfer, Till; Franken, Christina; Rohland, Hendrik; Hutterer, Rainer; Erdenebat, Ulambayar; Batbayar, Tumurochir (Journal of Global Archaeology, 2023)
FOLGt ... : Journal of Global Archaeology, 2023 ...